AVALIAÇÃO DA BIOCOMPATIBILIDADE DE 4 CIMENTOS ENDODÔNTICOS:ESTUDO EM TECIDO CONJUNTIVO SUBCUTÂNEO DE RATOS - Silveira, Camila Maggi Maia (2008)
The purpose of this study was evaluate the biocompatibility of four root canal sealers, Epiphany, AH Plus, Pulp Canal Sealer, Sealapex. Sterile polyethylene tubes containing freshly mixed test materials were inserted into the connective tissues of the sixty rats. The animals were divided into four groups. After anesthesia, the dorsal skin was shaved, disinfected, incisioned and two pocket were carefully prepared by blunt dissection and each animal received two implantations in opposite sides, one containing the material nd another as control (empty polyethylene tube). After periods of 7, 15 and 30 days, the implants were removed with the surrounding tissue and immersed in 10% formalin solution for 48 hours. After fixing the tissue it was processed for paraffin embedding which were cut in serial sections with the microtome set at 4 μm, stained with hematoxylin and eosin and assessed by light microscopy. The descriptive analysis was conducted by a pathologist who was blinded to which group and experimental period the glass slides pertained to, following the criteria: A) the thickness of the fibrous capsule: thin, intermediate or thick; B) Connective tissue composition: fibrous or loose, necrosis, nerve, blood vessels; C) the severity of the inflammatory reaction: mild, moderate, severe; D) presence of giant cells. The results revealed that after a period of 7 days all the sealers induced moderate-to-severe inflammatory reaction and Sealapex presented mild inflammatory reaction. At the 15-day, Epiphany and AH Plus sealers conducted to moderate inflammatory reaction, Pulp Canal Sealer severe inflammatory reaction, and Sealapex had the same intensity. After 30 days of the implantation of the sealers, mild inflammatory reactions were observed for the Epiphany, AH Plus and Sealapex, and moderate inflammatory reaction for the Pulp Canal Sealer. The results of this study revealed that Sealapex presented lowest level of inflammatory reaction in all the observed periods, yet all the sealers induced acceptable biological compatibility. More extensive experiments will be necessary to fully predict the clinical behavior of the sealers in patients undergoing endodontic therapy.